'Personal data literacies': A critical literacies approach to enhancing understandings of personal digital data. (February 2019) - Pangrazio, Luci; Selwyn, Neil
The capacity to understand and control one's personal data is now a crucial part of living in contemporary society. In this sense, traditional concerns over supporting the development of 'digital literacy' are now being usurped by concerns over citizens' 'data literacies'. In contrast to recent data safety and data science approaches, this article argues for a more critical form of 'personal data literacies' where digital data are understood as socially situated and context dependent. Drawing on the critical literacies tradition, the article outlines a range of salient socio-technical understandings of personal data generation and processing. Specifically, the article proposes a framework of 'Personal Data Literacies' that distinguishes five significant domains: (1) Data Identification, (2) Data Understandings, (3) Data Reflexivity, (4) Data Uses, and (5) Data Tactics. The article concludes by outlining the implications of this framework for future education and research around the area of individuals' understandings of personal data.